1998
DOI: 10.1200/jco.1998.16.5.1826
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of paclitaxel, fluorouracil, and cisplatin in patients with advanced carcinoma of the esophagus.

Abstract: The combination of paclitaxel, cisplatin, and 5-FU has substantial antitumor activity in metastatic esophageal carcinoma, with a remarkable complete response rate noted in patients with squamous carcinoma. Paclitaxel is an important new agent in the treatment of esophageal carcinoma, and further evaluation of this agent in combination chemotherapy is warranted. Given the toxicity associated with the current regimen, the optimal dose and schedule of paclitaxel in combination chemotherapy remain to be establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
130
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(137 citation statements)
references
References 12 publications
4
130
0
3
Order By: Relevance
“…A similar favourable response rate of 51% with a median survival time of 6 months was recently achieved by Kim et al (1999) administering paclitaxel at a dose of 175 mg/m 2 on day 1, 5-FU at a dose of 750 mg/m 2 on days 1-5 as continuous infusion and cisplatin at a dose of 20 mg/m 2 as a 30 minute infusion on days 1-5. In patients with adenocarcinoma of the oesophagus, Ilson et al (1998) reported a response rate of 46% with a similar schedule. The median overall and progression-free survival of 14 and 9 months duration, respectively, in the current study are encouraging.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar favourable response rate of 51% with a median survival time of 6 months was recently achieved by Kim et al (1999) administering paclitaxel at a dose of 175 mg/m 2 on day 1, 5-FU at a dose of 750 mg/m 2 on days 1-5 as continuous infusion and cisplatin at a dose of 20 mg/m 2 as a 30 minute infusion on days 1-5. In patients with adenocarcinoma of the oesophagus, Ilson et al (1998) reported a response rate of 46% with a similar schedule. The median overall and progression-free survival of 14 and 9 months duration, respectively, in the current study are encouraging.…”
Section: Discussionmentioning
confidence: 98%
“…A high response rate combined with an acceptable toxicity was reported (Belani et al, 1997;Ilson et al, 1998).…”
mentioning
confidence: 99%
“…Ilson et al (1998) treated 61 patients with the combination of paclitaxel 175 mg m 72 administered over 3 h on day 1, cisplatin 20 mg m 72 days 1 -5 and 5-fluorouracil 1000 mg m 72 days 1 -5; 48% of the patients had to be admitted for reasons of toxicity. In a subsequent study 5-fluorouracil was omitted and paclitaxel 200 -250 mg m 72 was administered over 24 h followed by cisplatin 75 mg m 72 (Ilson et al, 2000). Cycles were repeated every 3 weeks and all patients received granulocyte colony stimulating factor support.…”
Section: Clinicalmentioning
confidence: 99%
“…Thus, there is a need for tolerable and active protocols beyond cisplatin-based therapy. Irinotecan and taxanes proved to induce remissions in oesophageal cancer (Ilson et al, 1998(Ilson et al, , 1999 although single-agent docetaxel revealed only moderate activity (Heath et al, 2002). The combination of irinotecan and docetaxel has been investigated in phase I studies in patients with pretreated solid tumours (Adjei et al, 2000;Couteau et al, 2000).…”
mentioning
confidence: 99%